DEVELOPMENT OF COMMUNICATIVE COMPETENCES IN STUDENTS BY TRAINING PROGRAMS - A. V. Lazareva (Vestnik MGIMO-Universiteta)
The author of the article considers the possibility of enhancing students' motivation and development of their communicative competences in a group work, carried out as a psycholinguistic training in the language of speciality. A psycholinguistic training is treated by the author as an active psychological as well as pedagogical method of influence which further on optimizes professional interaction, self-growth, development of leadership qualities and skills of cooperation. The training carried out in the language of speciality (namely English) signaficantly enhanced the participants' motivation to language learning, oral skills development, language barriers removing, as well as accumulation of positive experience towards oneself and others, communication at large. During the training group work all the participants demonstrated all the stages of group dynamic, high level of performance and emotional involvement into the process. As the author marks out, it is the emotional involvement that positively effected the participants' interaction, their self-realization and language barriers removing. In the training program the following methods were involved: discussion (braistorming, case study, method of synectics), role plays, business role plays, art-therapy and metaforization of the accumulated experience. The results of this experiment prove that such combined programs could be effectively applied in Higher education curriculum.